PENERAPAN METODE PENEMUAN TERBIMBING UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI GRADIEN DI KELAS VIII SMP NEGERI 9 PALU - Yusnawan, Putu Adi (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
Abstract: The problem of low student understanding on the items gradient is an important aspect in teaching and learning mathematics. This research was conducted with the aim of obtaining a description of the application of reinvention Â methods which can increase student understanding of the items gradient in class VIII SMP Negeri 9 Palu. To improve students understanding of the items gradient, done with class action research refers to the model of Kemmis and Mc. Taggart which consists of four components, namely: 1) planning, 2) implementation of the action, 3) observation, 4) reflection. The results of this study indicate that two cycles are carried out to increase understanding according to indicators of the success of the action, taken through reinvention method with the following steps: 1) formulation of the problem, 2) data processing, 3) the preparation of the provisional estimates (conjecture), 4) examination of provisional estimates; 5) verbalization provisional estimates; 6) feedback.